OBJECTS OF TRANSPORT INFRASTRUCTURE: EXPERIENCE OF SCIENTIFIC SUPPORT IN CONSTRUCTION WITHIN THE “QUALITY” CONCEPT IMPLEMENTATION - I. S. Pulyaev; S. M. Pulyaev (Вестник СибАДИ, 2019)
Introduction. The paper deals with the issues related to the implementation of the “quality” concept in the construction of reinforced concrete transport facilities linked with the scientific support during design and construction. Nowadays this problem particularly relevant in the context of the modern construction solutions, combined with the need to obtain the required properties of concrete structures and ensure the economic feasibility of construction. The aim of the research is to generalize and systematize the main methods and techniques of concrete works, which minimize the defects and cracks while the construction of transport infrastructure.Materials and methods. On the example of different technologies used in the Russian construction over last 10 years, the authors demonstrated the developed methods of obtaining high quality concrete products taking into account tested and proved modern building materials.Results. The results of the research formed the basis of the projects, technological regulations for the production, specifications and standards of organizations, guidelines. Moreover, the results also allowed implementing the concept of “quality” in transport construction based on obtaining defect-free reinforced concrete structures with specified properties, taking into account the use of modern building materials.Discussion and conclusions. The research allows carrying out construction of various massiveness and extent. The obtained results form the basis of construction technology of other industrial and civil construction objects with reinforced concrete application. The paper is interesting and useful for specialists in providing defect-free construction of reinforced concrete building structures, for engineering and technical staff. The authors dedicate the research to the memory of Professor and Doctor of Technical Sciences, A.R. Solovyanchik (1938-2019).